2021
DOI: 10.3389/fphys.2021.723853
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Overexpression Induces Hyperphagia and Intestinal Morphophysiological Adaptations to Improve Nutrient Uptake in Zebrafish

Abstract: Graphical AbstractGH overexpression increases the intestinal mass and absorptive surface area both through the direct effects of GH transgenics (up-regulating the expression of its cognate receptor and insulin-like growth factor, igf1a) and through indirect effects through an increase in the amount of food consumed. In addition, hyperphagia provides a greater amount of nutrients in the intestinal lumen and stimulates the synthesis of di- and tri-peptide transporters, which are the main route of absorption of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…In addition, we found that overexpression of GH upregulated the expression level of the glucose transport protein-related genes ( glut2 and sglt1 ) and the fatty-acid transport protein-related genes ( fabp2 and cd36 ) in intestine and the expression level of the peptide transport protein-related gene pept1 in foregut and midgut. This was also observed in GH-treated tilapia and GH -transgenic zebrafish ( 18 , 19 ). The increased absorptive area and enhanced transport capacity could result in greater intestinal absorption of small molecular nutrients in T carp when compared to in WT carp.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, we found that overexpression of GH upregulated the expression level of the glucose transport protein-related genes ( glut2 and sglt1 ) and the fatty-acid transport protein-related genes ( fabp2 and cd36 ) in intestine and the expression level of the peptide transport protein-related gene pept1 in foregut and midgut. This was also observed in GH-treated tilapia and GH -transgenic zebrafish ( 18 , 19 ). The increased absorptive area and enhanced transport capacity could result in greater intestinal absorption of small molecular nutrients in T carp when compared to in WT carp.…”
Section: Discussionsupporting
confidence: 56%
“…The coefficient of determination (R-squared, R 2 ) was also calculated for each dataset. genetic manipulations [28] wild-type and gh-transgenic zebrafish from the F0104 lineage growth hormone overexpression Increased in gh-transgenic zebrafish line [30] wild-type and gh-transgenic zebrafish from the F0104 lineage growth hormone overexpression Increased in gh-transgenic zebrafish line Increased in insra −/− and insrb −/− zebrafish lines [56] wild-type AB strain and homozygous edar mutants knockout of ectodysplasin-A receptor (edar)…”
Section: Factors Affecting Zebrafish Feed Intakementioning
confidence: 99%
“…Moreover, changes in water salinity modulate the expression levels of genes of the somatic growth axis in salmonids (213), blackhead sea bream (Acanthopagrus schlegelii) (233), gilthead sea bream (234), tilapia (Oreochromis mossambicus) (235), and pejerrey (Odontesthes bonariensis) (236). Furthermore, high salinity increases food intake (237, 238), perhaps stimulated directly by GH or indirectly through the metabolic effects of GH (75, 239,240). Moreover, GH improves nutrient absorption at the gut level (241) which can explain the observed increase in feed efficiency.…”
Section: Salinitymentioning
confidence: 99%
“…Furthermore, high salinity increases food intake ( 237 , 238 ), perhaps stimulated directly by GH or indirectly through the metabolic effects of GH ( 75 , 239 , 240 ). Moreover, GH improves nutrient absorption at the gut level ( 241 ) which can explain the observed increase in feed efficiency.…”
Section: External Regulation Of Endocrine Factors Controlling Growth ...mentioning
confidence: 99%